Heparin: The Silver Bullet of Aneurysmal Subarachnoid Hemorrhage? - Khattar, Nicolas K.; James, Robert F. (Frontiers in Neurology, 2018)
Various neurological diseases have recently been associated with neuro-inflammation and worsening outcomes. Subarachnoid hemorrhage has been shown to generate a potent neuro-inflammatory response. Heparin is a potential effective anti-inflammatory agent to prevent initial injury as well as delayed neurological decline. Different mechanisms of action for heparin have been proposed including, but not limited to the binding and neutralization of oxy-hemoglobin, decreased transcription and signal transduction of endothelin-1, inhibition of binding to vessel wall selectins and vascular leakage into the subarachnoid space as well as direct binding and neutralization of inflammatory molecules. With a reasonably safe side-effect profile, heparin has shown significant promise in small series in human studies of aneurysmal subarachnoid hemorrhage in decreasing both initial and delayed neurological injury. Further studies are needed to validate the variety of neuroprotective features of heparin in subarachnoid hemorrhage as well as other disease states.